Efficacy of Indigenous Strains of Entomopathogenic Nematodes in Controlling the Eggplant Fruit and Shoot Borer Leucinodes orbonalis - Salma Javed; Sajjad Ali; Connor J. Goldy; Bushra Nawab; Anil Baniya; Adler R. Dillman (Insects)
The growing reliance on chemical pesticides in agriculture has raised significant concerns about their environmental and health impacts. This study investigates the potential of Indigenous entomopathogenic nematodes (EPNs), specifically Steinernema pakistanense and Heterorhabditis indica, as biological control agents for Leucinodes orbonalis, the brinjal fruit and shoot borer, a major pest in Karachi, Sindh, Pakistan. A comprehensive soil sampling was carried out across 30 locations. Molecular identification via PCR and sequencing confirmed the taxonomic classification of the isolated strains, showing high genetic similarity to known EPN species. The reproductive potential of the isolated strains varied, with Pak.S.SA.22 exhibiting the highest fecundity, averaging 91,944 offspring per larva, indicating strong biocontrol potential. Laboratory bioassays at different concentrations showed that Pak.S.SA.22 achieved 100% mortality of L. orbonalis at a concentration of 200 IJs/mL, confirming its effectiveness. Field trials further validated these findings, demonstrating up to 90% pest control efficacy over multiple application intervals, highlighting the practical applicability of this strain in field conditions. These results advocate for the inclusion of indigenous EPNs in integrated pest management (IPM) programs as a sustainable, environmentally friendly alternative to chemical pesticides, contributing to the promotion of sustainable agricultural practices.